(untitled) (Bangladesh Journal of Medical Science, 2014)
Objectives: To study the association of attention-deficit hyperactivity disorder (ADHD) with heroin addiction. Study design: A cross-sectional, hospital based study. Place and duration of study: The study was carried out at Lady Reading Hospital and Khyber Teaching Hospital, Peshawar, Pakistan from 4th April 2012 to 13th September 2012. Subjects and Methods: A sample of 137 adult heroin addicts were analyzed that whether they were ADHD and that childhood problem continues to manifest symptoms in adults. For retrospective assessment of childhood ADHD, the Wender Utah Rating Scale (WURS) as well as the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) symptom checklist for ADHD was used. The Conners Adult ADHD Rating Scales (CAARS) was used to assess the persisting symptoms of ADHD in adults. Inclusion criteria: Patient diagnosed with heroin addiction according to ICD-9 and DSM-IV. Exclusion criteria: Patient has co-morbid with any other mental illnesses. Results: The difference between the mean score of WURS and CAARS of ADHD patients were significantly greater than the normal patients. Heroin addicts showed 41.6% (WURS) and 38.6% (DSM-IV diagnostic criteria) that indicated evidence of retrospective ADHD affliction in childhood. 22.6% were IV users. CAARS was presented in 37.9% heroin addicts who exhibited a substantiation of ADHD persistent in adulthood. The difference between the mean score of WURS and CAARS of ADHD patients were significantly greater (P = 0.003), than the normal patients. Conclusions: These results revealed that addiction is associated with co-morbidity with ADHD, expressed in the form of heroin addiction. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18294 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.128-134